Depigmented Allergoids Reveal New Epitopes with Capacity to Induce IgG Blocking Antibodies. (8th October 2013) - López-Matas, M. Angeles; Gallego, Mayte; Iraola, Víctor; Robinson, Douglas; Carnés, Jerónimo
Abstract : Background . The synthesis of allergen-specific blocking IgGs that interact with IgE after allergen immunotherapy (SIT) has been related to clinical efficacy. The objectives were to investigate the epitope specificity of IgG-antibodies induced by depigmented-polymerized (Dpg-Pol) allergoids and unmodified allergen extracts, and examine IgE-blocking activity of induced IgG-antibodies. Methods . Rabbits were immunized with native and Dpg-Pol extracts of birch pollen, and serum samples were obtained. Recognition of linear IgG-epitopes of Bet v 1 and Bet v 2 and the capacity of these IgG-antibodies to block binding of human-IgE was determined. Results . Serum from rabbits immunized with native extracts recognised 11 linear epitopes from Bet v 1, while that from Dpg-Pol-immunized animals recognised 8. For Bet v 2, 8 epitopes were recognized by IgG from native immunized animals, and 9 from Dpg-Pol immunized one. Dpg-Pol and native immunized serum did not always recognise the same epitopes, but specific-IgG from both could block human-IgE binding sites for native extract. Conclusions . Depigmented-polymerized birch extract stimulates the synthesis of specific IgG-antibodies which recognize common but also novel epitopes compared with native extracts. IgG-antibodies induced by Dpg-Pol effectively inhibit human-IgE binding to allergens which may be part of the mechanism of action of SIT.